Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Continent-wide stock structure and connectivity of silver trevally (Pseudocaranx georgianus) based on population genomics and otolith shape and chemistry - Zoriana H.T. Lam; John Stewart; Jonathan Sandoval-Castillo; Patrick Reis-Santos; Rhiannon A. Van Eck; Bronwyn M. Gillanders; Peter Ritchie; Maren Wellenreuther; Charlie Huveneers; David V. Fairclough; Ashley M. Fowler; Julian Hughes; et al. (Fisheries Research, 2026)

Deployment of portable, modular gas samplers as part of an atmospheric tracer experiment - Khiloni A. Shah; Nathan D. Anderson; Paul M. Baltoi; JohnPeter Bekker; Sarah T. Castro; Grayson N. Constantine; George J. Coutoumanos; Ethan P. Fowler; Kevin A. Guerra; Clayton C. Hudson; Nicholas M. Kaitschuck; John B. Lyle; et al. (Journal of Environmental Radioactivity, 2025)

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

The origin and water quality of spring systems in Monchique, Portugal: A focus on Long-Term sustainability and elevated sodium levels - M.A. Hoque; K.B. Amponsah; A. Blum; N. Walton; P. Dennis; A.P. Butler; S. Hugman; A. Bamberger; M. Fowler (Journal of Hydrology, 2024)

Human‐modified habitats imperil ornamented dragonflies less than their non‐ornamented counterparts at local, regional, and continental scales - Michael P. Moore; Noah T. Leith; Kasey D. Fowler‐Finn; Kim A. Medley (Ecology Letters, 2024)
Biologists have long wondered how sexual ornamentation influences a species' risk of extinction. Because the evolution of condition‐dependent ornamentation can reduce intersexual conflict and accelerate the fixation of advantageous alleles, some theory predicts that ornamented taxa can be buffered against extinction in novel and/or stressful environments. Nevertheless, evidence from the wild remains limited. Here, we show that ornamented dragonflies are less vulnerable to extinction across multiple spatial scales. Population‐occupancy models across the Western United States reveal that ornamented species have become more common relative to non‐ornamented species over >100 years. Phylogenetic analyses indicate that ornamented species exhibit lower continent‐wide extinction risk than non‐ornamented species. Finally, spatial analyses of local dragonfly assemblages suggest that ornamented species possess advantages over non‐ornamented taxa at living in habitats that have been converted to farms and cities. Together, these findings suggest that ornamented taxa are buffered against contemporary extinction at local, regional, and continental scales.

Developing expert scientific consensus on the environmental and societal effects of marine artificial structures prior to decommissioning - Antony M. Knights; Anaëlle J. Lemasson; Louise B. Firth; Todd Bond; Jeremy Claisse; Joop W.P. Coolen; Andrea Copping; Jennifer Dannheim; Michela De Dominicis; Steven Degraer; Michael Elliott; Paul G. Fernandes; et al. (Journal of Environmental Management, 2024)

Quantification and classification of a giant fluvial-distributive system - the Triassic Mungaroo Formation, NWS, Australia - T.H.D. Payenberg; B.J. Willis; P. Sixsmith; S.D. Connell; A. Powell; K.T. Milliken; H.W. Posamentier; A. Allgoewer; E. Meyers; T. Marsh; M.D. Sullivan; S.C. Lang; et al. (Earth-Science Reviews, 2024)

Toward sustainable harvest strategies for marine fisheries that include recreational fishing - Ashley M. Fowler; Natalie A. Dowling; Jeremy M. Lyle; Josep Alós; Leif E. Anderson; Steven J. Cooke; Andy J. Danylchuk; Keno Ferter; Heath Folpp; Clifford Hutt; Kieran Hyder; Daniel K. Lew; et al. (Fish and Fisheries, 2023)
Recreational fishing (RF) is a large yet undervalued component of fisheries globally. While progress has been made in monitoring, assessing, and managing the sector in isolation, integration of RF into the management of multi‐sector fisheries has been limited, particularly relative to the commercial sector. This marginalises recreational fishers and reduces the likelihood of achieving the sector's objectives and, more broadly, achieving fisheries sustainability. We examined the nature and extent of RF inclusion in harvest strategies (HSs) for marine fisheries across 15 regions in 11 nations to define the gap in inclusion that has developed between sectors. We focused on high‐income nations with a high level of RF governance and used a questionnaire to elicit expert knowledge on HSs due to the paucity of published documents. In total, 339 HSs were considered. We found that RF inclusion in HSs was more similar to the small‐scale sector (i.e., artisanal, cultural, or subsistence) than the commercial sector, with explicit operational objectives, data collection, performance indicators, reference points, and management controls lacking in many regions. Where specified, RF objectives focused on sustainability, economic value and catch allocation rather than directly relating to the recreational fishing experience. Conflicts with other sectors included competition with the commercial sector for limited resources, highlighting the importance of equitable resource allocation policies alongside HSs. We propose that RF be explicitly incorporated into HSs to ensure fisheries are ecologically, economically, and socially sustainable, and we recommend that fisheries organisations urgently review HSs for marine fisheries with a recreational component to close the harvest strategy gap among sectors.

Extensive regional variation in the phenology of insects and their response to temperature across N orth A merica - Peter O. Dunn; Insiyaa Ahmed; Elise Armstrong; Natasha Barlow; Malcolm A. Barnard; Marc Bélisle; Thomas J. Benson; Lisha L. Berzins; Chloe K. Boynton; T. Anders Brown; Melissa Cady; Kyle Cameron; et al. (Ecology, 2023)
Climate change models often assume similar responses to temperatures across the range of a species, but local adaptation or phenotypic plasticity can lead plants and animals to respond differently to temperature in different parts of their range. To date, there have been few tests of this assumption at the scale of continents, so it is unclear if this is a large‐scale problem. Here, we examined the assumption that insect taxa show similar responses to temperature at 96 sites in grassy habitats across North America. We sampled insects with Malaise traps during 2019–2021 ( N = 1041 samples) and examined the biomass of insects in relation to temperature and time of season. Our samples mostly contained Diptera (33%), Lepidoptera (19%), Hymenoptera (18%), and Coleoptera (10%). We found strong regional differences in the phenology of insects and their response to temperature, even within the same taxonomic group, habitat type, and time of season. For example, the biomass of nematoceran flies increased across the season in the central part of the continent, but it only showed a small increase in the Northeast and a seasonal decline in the Southeast and West. At a smaller scale, insect biomass at different traps operating on the same days was correlated up to ~75 km apart. Large‐scale geographic and phenological variation in insect biomass and abundance has not been studied well, and it is a major source of controversy in previous analyses of insect declines that have aggregated studies from different locations and time periods. Our study illustrates that large‐scale predictions about changes in insect populations, and their causes, will need to incorporate regional and taxonomic differences in the response to temperature.

Conservation of endangered galaxiid fishes in the Falkland Islands requires urgent action on invasive brown trout - J. F. Minett; D. M. Fowler; J. A. H. Jones; P. Brickle; G. T. Crossin; S. Consuegra; C. Garcia de Leaniz (Biological Invasions, 2023)
Non-native salmonids are protected in the Southern hemisphere where they sustain aquaculture and lucrative sport fisheries, but also impact many native fishes, which poses a conservation conundrum. Legal protection and human-assisted secondary releases may have helped salmonids to spread, but this has seldom been tested. We reconstructed the introduction of brown trout ( Salmo trutta ) to the Falkland Islands using historical records and modelled its dispersal and probability of invasion using a generalized linear model and Leave One out Cross Validation. Our results indicate that establishment success was ~ 88%, and that dispersal was facilitated over land by proximity to invaded sites and density of stream-road crossings, suggesting it was human assisted. Brown trout have already invaded 54% of Falkland rivers, which are 2.9–4.5 times less likely to contain native galaxiids than uninvaded streams. Without strong containment we predict brown trout will invade nearly all suitable freshwater habitats in the Falklands within the next ~ 70 years, which might put native freshwater fishes at a high risk of extinction.

Targeting de novo loss-of-function variants in constrained disease genes improves diagnostic rates in the 100,000 Genomes Project - Eleanor G. Seaby; N. Simon Thomas; Amy Webb; Helen Brittain; Ana Lisa Taylor Tavares; J. C. Ambrose; P Arumugam; R Bevers; M Bleda; F Boardman-Pretty; C. R. Boustred; H Brittain; et al. (Human Genetics, 2023)
Background Genome sequencing was first offered clinically in the UK through the 100,000 Genomes Project (100KGP). Analysis was restricted to predefined gene panels associated with the patient’s phenotype. However, panels rely on clearly characterised phenotypes and risk missing diagnoses outside of the panel(s) applied. We propose a complementary method to rapidly identify pathogenic variants, including those missed by 100KGP methods. Methods The Loss-of-function Observed/Expected Upper-bound Fraction (LOEUF) score quantifies gene constraint, with low scores correlated with haploinsufficiency. We applied DeNovoLOEUF, a filtering strategy to sequencing data from 13,949 rare disease trios in the 100KGP, by filtering for rare, de novo, loss-of-function variants in disease genes with a LOEUF score < 0.2. We compared our findings with the corresponding patient’s diagnostic reports. Results 324/332 (98%) of the variants identified using DeNovoLOEUF were diagnostic or partially diagnostic (whereby the variant was responsible for some of the phenotype). We identified 39 diagnoses that were “missed” by 100KGP standard analyses, which are now being returned to patients. Conclusion We have demonstrated a highly specific and rapid method with a 98% positive predictive value that has good concordance with standard analysis, low false-positive rate, and can identify additional diagnoses. Globally, as more patients are being offered genome sequencing, we anticipate that DeNovoLOEUF will rapidly identify new diagnoses and facilitate iterative analyses when new disease genes are discovered.

Advancing the scholarship and practice of stakeholder engagement in working landscapes: a co-produced research agenda - Weston M. Eaton; Morey Burnham; Tahnee Robertson; J. G. Arbuckle; Kathryn J. Brasier; Mark E. Burbach; Sarah P. Church; Georgia Hart-Fredeluces; Douglas Jackson-Smith; Grace Wildermuth; Katherine N. Canfield; S. Carolina Córdova; et al. (Socio-Ecological Practice Research, 2022)
Participatory approaches to science and decision making, including stakeholder engagement, are increasingly common for managing complex socio-ecological challenges in working landscapes. However, critical questions about stakeholder engagement in this space remain. These include normative, political, and ethical questions concerning who participates, who benefits and loses, what good can be accomplished, and for what, whom, and by who. First, opportunities for addressing justice, equity, diversity, and inclusion interests through engagement, while implied in key conceptual frameworks, remain underexplored in scholarly work and collaborative practice alike. A second line of inquiry relates to research–practice gaps. While both the practice of doing engagement work and scholarly research on the efficacy of engagement is on the rise, there is little concerted interplay among ‘on-the-ground’ practitioners and scholarly researchers. This means scientific research often misses or ignores insight grounded in practical and experiential knowledge, while practitioners are disconnected from potentially useful scientific research on stakeholder engagement. A third set of questions concerns gaps in empirical understanding of the efficacy of engagement processes and includes inquiry into how different engagement contexts and process features affect a range of behavioral, cognitive, and decision-making outcomes. Because of these gaps, a cohesive and actionable research agenda for stakeholder engagement research and practice in working landscapes remains elusive. In this review article, we present a co-produced research agenda for stakeholder engagement in working landscapes. The co-production process involved professionally facilitated and iterative dialogue among a diverse and international group of over 160 scholars and practitioners through a yearlong virtual workshop series. The resulting research agenda is organized under six cross-cutting themes: (1) Justice, Equity, Diversity, and Inclusion; (2) Ethics; (3) Research and Practice; (4) Context; (5) Process; and (6) Outcomes and Measurement. This research agenda identifies critical research needs and opportunities relevant for researchers, practitioners, and policymakers alike. We argue that addressing these research opportunities is necessary to advance knowledge and practice of stakeholder engagement and to support more just and effective engagement processes in working landscapes.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Influence of offshore oil and gas structures on seascape ecological connectivity - Dianne L. McLean; Luciana C. Ferreira; Jessica A. Benthuysen; Karen J. Miller; Marie‐Lise Schläppy; Matthew J. Ajemian; Oliver Berry; Silvana N. R. Birchenough; Todd Bond; Fabio Boschetti; Ann S. Bull; Jeremy T. Claisse; et al. (Global Change Biology, 2022)
Offshore platforms, subsea pipelines, wells and related fixed structures supporting the oil and gas (O&G) industry are prevalent in oceans across the globe, with many approaching the end of their operational life and requiring decommissioning. Although structures can possess high ecological diversity and productivity, information on how they interact with broader ecological processes remains unclear. Here, we review the current state of knowledge on the role of O&G infrastructure in maintaining, altering or enhancing ecological connectivity with natural marine habitats. There is a paucity of studies on the subject with only 33 papers specifically targeting connectivity and O&G structures, although other studies provide important related information. Evidence for O&G structures facilitating vertical and horizontal seascape connectivity exists for larvae and mobile adult invertebrates, fish and megafauna; including threatened and commercially important species. The degree to which these structures represent a beneficial or detrimental net impact remains unclear, is complex and ultimately needs more research to determine the extent to which natural connectivity networks are conserved, enhanced or disrupted. We discuss the potential impacts of different decommissioning approaches on seascape connectivity and identify, through expert elicitation, critical knowledge gaps that, if addressed, may further inform decision making for the life cycle of O&G infrastructure, with relevance for other industries (e.g. renewables). The most highly ranked critical knowledge gap was a need to understand how O&G structures modify and influence the movement patterns of mobile species and dispersal stages of sessile marine species. Understanding how different decommissioning options affect species survival and movement was also highly ranked, as was understanding the extent to which O&G structures contribute to extending species distributions by providing rest stops, foraging habitat, and stepping stones. These questions could be addressed with further dedicated studies of animal movement in relation to structures using telemetry, molecular techniques and movement models. Our review and these priority questions provide a roadmap for advancing research needed to support evidence‐based decision making for decommissioning O&G infrastructure.

Assessment of Australian Sea Lion Bycatch Mortality in a Gillnet Fishery, and Implementation and Evaluation of an Effective Mitigation Strategy - Simon D. Goldsworthy; Brad Page; Derek J. Hamer; Andrew D. Lowther; Peter D. Shaughnessy; Mark A. Hindell; Paul Burch; Daniel P. Costa; Shannon L. Fowler; Kristian Peters; Rebecca R. McIntosh; Frederic Bailleul; et al. (Frontiers in Marine Science, 2022)
Globally, the bycatch of marine mammals in fisheries represents the greatest source of human-caused mortality that threatens the sustainability of many populations and species. The Australian sea lion ( Neophoca cinerea ) is an endangered species, whose populations off South Australia (SA) have been subject to bycatch in a demersal gillnet fishery targeting sharks since the 1960s. A comprehensive assessment was undertaken of sea lion bycatch mortality that combined independent fishery observer data with species distribution models (underpinned by satellite tracking, abundance data and population modeling) to model the relationship between at-sea foraging effort and bycatch rate. Combined with the distribution of fishing effort, these models enabled the overall level of bycatch mortality to be estimated by age, sex and subpopulation, facilitating population viability analyses that indicated most subpopulations were declining, and subject to unsustainable levels of bycatch mortality. To reduce this mortality, the Australian Fisheries Management Authority implemented an Australian Sea Lion Management Strategy that included an independent observer program (ultimately 100% electronic monitoring of gillnet fishing off SA), permanent spatial gillnet closures around all sea lion breeding sites, bycatch mortality limits that triggered temporal (18 months) spatial closures when zone-specific bycatch trigger limits were reached, and incentives for gillnet fishers to switch to an alternate fishing method (longlines). The Strategy had immediate impacts on the fishery: it resulted in significant reductions in gillnet fishing effort and on the reported bycatch of sea lions. In the next decade, there was an estimated 98% reduction in sea lion bycatch mortality from gillnet interactions and an apparent stabilization of the decline in sea lion pup abundances at some impacted breeding sites. There was an almost complete transition in the fishery from gillnets to longlines, and fishing catches returned to pre-management levels. The successful implementation of management measures to mitigate sea lion bycatch mortality in the gillnet fishery off SA was rapid, science informed, adaptive, comprehensive, and backed by strong compliance and monitoring of the fishery. It provides an important case study which demonstrates how management measures can be effectively applied to mitigate bycatch mortality of marine mammals and other marine protected species.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Increased expression of plasminogen activator inhibitor-1 (PAI-1) is associated with depression and depressive phenotype in C57Bl/6J mice - René A. Girard; Prashant S. Chauhan; Torry A. Tucker; Tim Allen; Jaswinder Kaur; Ann Jeffers; Kathleen Koenig; Galina Florova; Andrey A. Komissarov; Tatiana A. Gaidenko; Mignote B. Chamiso; James Fowler; et al. (Experimental Brain Research, 2019)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Global Observing Needs in the Deep Ocean - Lisa A. Levin; Brian J. Bett; Andrew R. Gates; Patrick Heimbach; Bruce M. Howe; Felix Janssen; Andrea McCurdy; Henry A. Ruhl; Paul Snelgrove; Karen I. Stocks; David Bailey; Simone Baumann-Pickering; et al. (Frontiers in Marine Science, 2019)

Primary central nervous system lymphoma in patients with and without HIV infection: a multicenter study and comparison with U.S national data - Dima Dandachi; Quinn T. Ostrom; Insun Chong; Jose A. Serpa; Thomas P. Giordano; Carol Kruchko; Jill S. Barnholtz-Sloan; Nathan Fowler; Rivka R. Colen; Fanny E. Morón (Cancer Causes & Control, 2019)

On-demand release of Candida albicans biofilms from urinary catheters by mechanical surface deformation - Stacey A. Maskarinec; Zehra Parlak; Qing Tu; Vrad Levering; Stefan Zauscher; Gabriel P. López; Vance G. Fowler; John R. Perfect (Biofouling, 2018)

Erratum to: Modelling foetal exposure to maternal smoking using hepatoblasts from pluripotent stem cells - Baltasar Lucendo-Villarin; Panagiotis Filis; Madeleine J. Swortwood; Marilyn A. Huestis; Jose Meseguer-Ripolles; Kate Cameron; John P. Iredale; Peter J. O’Shaughnessy; Paul A. Fowler; David C. Hay (Archives of Toxicology, 2017)

Modelling foetal exposure to maternal smoking using hepatoblasts from pluripotent stem cells - Baltasar Lucendo-Villarin; Panagiotis Filis; Madeleine J. Swortwood; Marilyn A. Huestis; Jose Meseguer-Ripolles; Kate Cameron; John P. Iredale; Peter J. O’Shaughnessy; Paul A. Fowler; David C. Hay (Archives of Toxicology, 2017)

Foraging strategies of a generalist marine predator inhabiting a dynamic environment - E. A. McHuron; P. W. Robinson; S. E. Simmons; C. E. Kuhn; M. Fowler; D. P. Costa (Oecologia, 2016)

Characterizing Uncertainty of the Hydrologic Impacts of Climate Change - Martyn P. Clark; Robert L. Wilby; Ethan D. Gutmann; Julie A. Vano; Subhrendu Gangopadhyay; Andrew W. Wood; Hayley J. Fowler; Christel Prudhomme; Jeffrey R. Arnold; Levi D. Brekke (Current Climate Change Reports, 2016)

Temperate predators and seasonal water temperatures impact feeding of a range expanding tropical fish - Hayden J. Beck; David A. Feary; Ashley M. Fowler; Elizabeth M. P. Madin; David J. Booth (Marine Biology, 2016)

Fatty acid mobilization and comparison to milk fatty acid content in northern elephant seals - Melinda A. Fowler; Cathy Debier; Eric Mignolet; Clementine Linard; Daniel E. Crocker; Daniel P. Costa (Journal of Comparative Physiology B, 2014)

Fish assemblages associated with oil industry structures on the continental shelf of north‐western Australia - N. Pradella; A. M. Fowler; D. J. Booth; P. I. Macreadie (Journal of Fish Biology, 2014)
This study provides the first assessment of fish associations with oil and gas structures located in deep water (85–175 m) on Australia's north‐west continental shelf, using rare oil industry video footage obtained from remotely operated vehicles. A diverse range of taxa were observed associating with the structures, including reef‐dependent species and transient pelagic species. Ten commercially fished species were observed, the most abundant of which was Lutjanus argentimaculatus , with an estimated biomass for the two deepest structures (Goodwyn and Echo) of 109 kg.

Risk factors for Staphylococcus aureus nasal colonization in Danish middle-aged and elderly twins - P. S. Andersen; L. A. Larsen; V. G. Fowler; M. Stegger; R. L. Skov; K. Christensen (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Genetic epidemiology of cardiometabolic risk factors and their clustering patterns in Mexican American children and adolescents: the SAFARI Study - Sharon P. Fowler; Sobha Puppala; Rector Arya; Geetha Chittoor; Vidya S. Farook; Jennifer Schneider; Roy G. Resendez; Ram Prasad Upadhayay; Jane VandeBerg; Kelly J. Hunt; Benjamin Bradshaw; Eugenio Cersosimo; et al. (Human Genetics, 2013)

Potential effects of climate change on biological control systems: case studies from New Zealand - P. J. Gerard; J. R. F. Barringer; J. G. Charles; S. V. Fowler; J. M. Kean; C. B. Phillips; A. B. Tait; G. P. Walker (BioControl, 2013)

Mobile receivers: releasing the mooring to ‘see’ where fish go - Sean A. Hayes; Nicole M. Teutschel; Cyril J. Michel; Cory Champagne; Patrick W. Robinson; Melinda Fowler; Tina Yack; David K. Mellinger; Samantha Simmons; Daniel P. Costa; R. Bruce MacFarlane (Environmental Biology of Fishes, 2013)

Methane emissions from soils: synthesis and analysis of a large UK data set - Peter E. Levy; Annette Burden; Mark D. A. Cooper; Kerry J. Dinsmore; Julia Drewer; Chris Evans; David Fowler; Jenny Gaiawyn; Alan Gray; Stephanie K. Jones; Timothy Jones; Niall P. McNamara; et al. (Global Change Biology, 2012)
Nearly 5000 chamber measurements of CH 4 flux were collated from 21 sites across the U nited K ingdom, covering a range of soil and vegetation types, to derive a parsimonious model that explains as much of the variability as possible, with the least input requirements. Mean fluxes ranged from −0.3 to 27.4 nmol CH 4 m −2 s −1 , with small emissions or low rates of net uptake in mineral soils (site means of −0.3 to 0.7 nmol m −2 s −1 ) and much larger emissions from organic soils (site means of −0.3 to 27.4 nmol m −2 s −1 ). Less than half of the observed variability in instantaneous fluxes could be explained by independent variables measured. The reasons for this include measurement error, stochastic processes and, probably most importantly, poor correspondence between the independent variables measured and the actual variables influencing the processes underlying methane production, transport and oxidation. When temporal variation was accounted for, and the fluxes averaged at larger spatial scales, simple models explained up to ca. 75% of the variance in CH 4 fluxes. Soil carbon, peat depth, soil moisture and pH together provided the best sub‐set of explanatory variables. However, where plant species composition data were available, this provided the highest explanatory power. Linear and nonlinear models generally fitted the data equally well, with the exception that soil moisture required a power transformation. To estimate the impact of changes in peatland water table on CH 4 emissions in the U nited K ingdom, an emission factor of +0.4 g CH 4 m −2 yr −1 per cm increase in water table height was derived from the data.

Stock discrimination of Southern Garfish (Hyporhamphus melanochir) by stable isotope ratio analysis of otolith aragonite - Mike A. Steer; Galen P. Halverson; Anthony J. Fowler; Bronwyn M. Gillanders (Environmental Biology of Fishes, 2010)

Epidemiology of influenza-associated hospitalization in adults, Toronto, 2007/8 - S. P. Kuster; S. Drews; K. Green; J. Blair; I. Davis; J. Downey; R. Fowler; K. Katz; S. Lapinsky; D. McRitchie; J. Pataki; J. Powis; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Clinical characteristics and outcomes of diabetic patients with Staphylococcus aureus bacteremia and endocarditis - Z. A. Kanafani; W. M. Kourany; V. G. Fowler; D. P. Levine; G. A. Vigliani; M. Campion; D. E. Katz; G. R. Corey; H. W. Boucher (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Transgenic mice expressing the Peripherin-EGFP genomic reporter display intrinsic peripheral nervous system fluorescence - Samuel McLenachan; Yona Goldshmit; Kerry J. Fowler; Lucille Voullaire; Timothy P. Holloway; Ann M. Turnley; Panos A. Ioannou; Joseph P. Sarsero (Transgenic Research, 2008)

Candida infective endocarditis - J. W. Baddley; D. K. Benjamin; M. Patel; J. Miró; E. Athan; B. Barsic; E. Bouza; L. Clara; T. Elliott; Z. Kanafani; J. Klein; S. Lerakis; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Prosthetic valve endocarditis due to coagulase-negative staphylococci: findings from the International Collaboration on Endocarditis Merged Database - T. Lalani; Z. A. Kanafani; V. H. Chu; L. Moore; G. R. Corey; P. Pappas; C. W. Woods; C. H. Cabell; B. Hoen; C. Selton-Suty; T. Doco-Lecompte; C. Chirouze; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2006)

Enterococcal prosthetic valve infective endocarditis: report of 45 episodes from the International Collaboration on Endocarditis-merged database - D. J. Anderson; L. Olaison; J. R. McDonald; J. M. Miro; B. Hoen; C. Selton-Suty; T. Doco-Lecompte; E. Abrutyn; G. Habib; S. Eykyn; P. A. Pappas; V. G. Fowler; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

Evaluation of an FRDA–EGFP genomic reporter assay in transgenic mice - Joseph P. Sarsero; Timothy P. Holloway; Lingli Li; Samuel McLenachan; Kerry J. Fowler; Ivan Bertoncello; Lucille Voullaire; Sophie Gazeas; Panos A. Ioannou (Mammalian Genome, 2005)

Human BAC-mediated rescue of the Friedreich ataxia knockout mutation in transgenic mice - Joseph P. Sarsero; Lingli Li; Timothy P. Holloway; Lucille Voullaire; Sophie Gazeas; Kerry J. Fowler; Denise M. Kirby; David R. Thorburn; Adam Galle; Surindar Cheema; Michel Koenig; Robert Williamson; et al. (Mammalian Genome, 2004)

Molecular and morphological analyses of the cuttlefish Sepia apama indicate a complex population structure - K. S. Kassahn; S. C. Donnellan; A. J. Fowler; K. C. Hall; M. Adams; P. W. Shaw (Marine Biology, 2003)

Biosphere-atmosphere interactions of ammonia with grasslands: Experimental strategy and results from a new European initiative - M.A. Sutton; C. Milford; E. Nemitz; M.R. Theobald; P.W. Hill; D. Fowler; J.K. Schjoerring; M.E. Mattsson; K.H. Nielsen; S. Husted; J.W. Erisman; R. Otjes; et al. (Plant and Soil, 2001)

Oxidation of atmospheric methane in Northern European soils, comparison with other ecosystems, and uncertainties in the global terrestrial sink - K. A. Smith; K. E. Dobbie; B. C. Ball; L. R. Bakken; B. K. Sitaula; S. Hansen; R. Brumme; W. Borken; S. Christensen; A. Priemé; D. Fowler; J. A. Macdonald; et al. (Global Change Biology, 2000)
Summary This paper reports the range and statistical distribution of oxidation rates of atmospheric CH 4 in soils found in Northern Europe in an international study, and compares them with published data for various other ecosystems. It reassesses the size, and the uncertainty in, the global terrestrial CH 4 sink, and examines the effect of land‐use change and other factors on the oxidation rate. Only soils with a very high water table were sources of CH 4 ; all others were sinks. Oxidation rates varied from 1 to nearly 200 μg CH 4 m −2 h −1 ; annual rates for sites measured for ≥1 y were 0.1–9.1 kg CH 4 ha −1 y −1 , with a log‐normal distribution (log‐mean ≈ 1.6 kg CH 4 ha −1 y −1 ). Conversion of natural soils to agriculture reduced oxidation rates by two‐thirds –‐ closely similar to results reported for other regions. N inputs also decreased oxidation rates. Full recovery of rates after these disturbances takes > 100 y. Soil bulk density, water content and gas diffusivity had major impacts on oxidation rates. Trends were similar to those derived from other published work. Increasing acidity reduced oxidation, partially but not wholly explained by poor diffusion through litter layers which did not themselves contribute to the oxidation. The effect of temperature was small, attributed to substrate limitation and low atmospheric concentration. Analysis of all available data for CH 4 oxidation rates in situ showed similar log‐normal distributions to those obtained for our results, with generally little difference between different natural ecosystems, or between short‐and longer‐term studies. The overall global terrestrial sink was estimated at 29 Tg CH 4 y −1 , close to the current IPCC assessment, but with a much wider uncertainty range (7 to > 100 Tg CH 4 y −1 ). Little or no information is available for many major ecosystems; these should receive high priority in future research.

Genetic diversity and gene flow among southeastern Queensland koalas ( Phascolarctos cinereus ) - E. V. Fowler; B. A. Houlden; P. Hoeben; P. Timms (Molecular Ecology, 2000)
Habitat fragmentation and destruction associated with the rapid urban and rural development of southeast Queensland presents an immediate threat to the survival of koala populations within this region. A sensitive method combining heteroduplex analysis (HDA) with temperature gradient gel electrophoresis (TGGE) was optimized to detect within‐species variation in a mitochondrial DNA (mtDNA) control‐region fragment, ≈ 670 bp in length, from the koala. Eight different haplotypes were characterized in koalas, of which four were novel. Analysis of mtDNA diversity in 96 koalas from five populations in southeast Queensland revealed that the number of haplotypes in a single population ranged from one to five, with an average within‐population haplotype diversity of 0.379 ± 0.016, and nucleotide diversity of 0.22 ± 0.001%. Nucleotide divergence between populations averaged 0.09 ± 0.001% and ranged from 0.00 to 0.14%. Significant genetic heterogeneity was observed among most populations, suggesting that koala populations may be spatially structured along matrilines, although this may not be universal. The limited distribution of the central phylogenetic haplotype suggested the possibility of historical population bottlenecks north of the Gold Coast, while the presence of two highly divergent haplotypes at the Moreton site may indicate the occurrence of one or more undocumented translocation events into this area.

The effect of termite biomass and anthropogenic disturbance on the CH 4 budgets of tropical forests in Cameroon and Borneo - J. A. Macdonald; D. Jeeva; P. Eggleton; R. Davies; D. E. Bignell; D. Fowler; J. Lawton; M. Maryati (Global Change Biology, 1999)
Summary The exchange of CH 4 between tropical forests and the atmosphere was determined by simultaneously measuring the net CH 4 flux at the soil surface and assessing the flux contribution from soil‐feeding termite biomass, both within the soil profile and in mounds. In Cameroon the flux of CH 4 ranged from a net emission of 40.7 ng m –2 s –1 to a net CH 4 oxidation of –53.0 ng m –2 s –1 . Soil‐inhabiting termite biomass was significantly correlated with CH 4 flux. Termite mounds emitted up to 2000 ng s –1 mound –1 . Termite‐derived CH 4 emission reduced the soil sink strength by up to 28%. Disturbance also had a strong effect on the soil sink strength, with the average rate of CH 4 oxidation, at – 17.5 ng m –2 s –1 , being significantly smaller (≈ 36%) at the secondary forest site than the –27.2 ng m –2 s –1 , observed at the primary forest site. CH 4 budgets calculated for each site indicated that both forests were net sinks for CH 4 at – 6.1 kg ha –1 y –1 in the near‐primary forest and – 3.1 kg ha –1 y –1 in the secondary forest. In Borneo, three forest sites representing a disturbance gradient were examined. CH 4 oxidation rates ranged from 0 to – 32.1 ng m –2 s –1 and a significant correlation between the net flux and termite biomass was observed only in an undisturbed primary forest, although the biomass was insufficient to cause net emission of CH 4 . Rates of CH 4 oxidation were not significantly different across the disturbance gradient but were, however, larger in the primary forest (averaging – 15.4 ng m –2 s –1 ) than in an old‐growth secondary forest (–13.9 ng m –2 s –1 ) and a young secondary re‐growth (– 10.8 ng m –2 s –1 ). CH 4 flux from termite mounds ranged from net oxidation in an abandoned mound to a maximum emission of 468 ng s –1 mound –1 . CH 4 budgets calculated for each site indicated that CH 4 flux from termite mounds had an insignificant effect on the budget of CH 4 at the regional scale at all three forest sites. Annual oxidation rates were – 4.8, – 4.2 and – 3.4 kg ha –1 y –1 in the primary, secondary and young secondary forests, respectively.

Age structure and diel activity of pouting on the Poole Bay artificial reef - A. J. Fowler; A. C. Jensen; K. J. Collins; I. P. Smith (Journal of Fish Biology, 1999)
Predominantly (86·6%) juvenile ( Trisopterus luscus formed inactive, nonfeeding schools around artificial reef units in Poole Bay, Dorset, during daylight hours and the position of the schools was related to differing tidal conditions. At current speeds >0·3 m s −1 , the pouting congregated close to the reef units, remained low in the water column and maintained position. At current speeds −1 , the schools were more dispersed, further away from reef units and higher in the water column. This tidally‐related behaviour is thought to be related to energy conservation during the daylight hours, when the pouting utilize the lee of reef units during strong tidal currents. Between 15 and 30 min after dusk the majority of pouting left the artificial reef, and returned 45–60 min before dawn. A brief mark‐recapture programme, using 0‐ to 1‐group pouting, confirmed that a proportion of the pouting tagged were present on the artificial reef up to 5 days after marking, suggesting that the site was being used to some extent as a home reef. The nocturnal foraging pattern may be related to the availability of prey species.

Deposition Monitoring in Europe - J. W. Erisman; M. G. Mennen; D. Fowler; C. R. Flechard; G. Spindler; A. Grüner; J. H. Duyzer; W. Ruigrok; G. P. Wyers (Environmental Monitoring and Assessment, 1998)

Genetic Variation in Captive Koalas (Phascolarctos cinereus): Parentage Determination and Individual Identification - E. V. Fowler; B. A. Houlden; W. B. Sherwin; P. Hoeben; P. Timms (Biochemical Genetics, 1998)